Lean Manufacturing Implementation Through Fuzzy Multi Criteria Decision-Making: A Literature Review - Amelia Hafsah Hutagalung; Aulia Ishak; Rosnani Ginting (TALENTA Publisher, 2025)
Lean manufacturing is a systematic approach to reduce waste and increase productivity. In its implementation, lean manufacturing is often faced with complexity in its application due to inappropriate decision-making. Therefore, a more structured approach, such as the integration of the Fuzzy Multi Criteria Decision-Making (FMCDM) method, is a solution to assist decision-making within the lean framework and ensure proper lean implementation. This research aims to explore the application of FMCDM by using a Systematic Literature Review (SLR) approach, successfully analyzing 185 articles published between 2000 and 2025 focusing on integrating FMCDM and lean manufacturing. The results of the literature review show that the integration of FMCDM and lean manufacturing is still limited but has increased since 2023, with FMCDM being used for three primary purposes, namely evaluation of factors and risks in lean implementation, selection of appropriate lean tools and strategies, and assessment of lean level. This research identifies research gaps and offers practical recommendations to improve lean manufacturing effectiveness through a more adaptive and structured decision-making approach. Thus, this research is expected to significantly contribute to developing lean manufacturing theory and practice, particularly in FMCDM-based decision-making.